The Rhetorical Dimensions of Kalam Khabari and Insya’i in Surah ‘Abasa and Their Implications for Educational Values - Kurnia, Wulan; Marlion, Ferki Ahmad; Refania, Zabila; Amanda, Ilda; Efiantri, Neza A (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2026)
This study aims to analyze the forms and rhetorical functions of Kalam Khabari and Kalam Insya’i in Surah ‘Abasa from the perspective of Arabic rhetoric (balaghah), particularly the branch of Ilm al-Ma‘ani. The research employs a qualitative approach using a library research method. The primary data source is the text of the Qur’an, specifically Surah ‘Abasa, while secondary data are obtained from classical tafsir books, rhetorical references, and relevant academic literature. Data collection was conducted through documentation by identifying and classifying the verses into categories such as Khabar Ibtida’i, Khabar Thalabi, Khabar Inkari, and various forms of Insya’i, including interrogative, imperative, exclamatory, and prohibitive expressions. The data were analyzed using a descriptive-analytical method to explain their linguistic structures and rhetorical values. Kalam khabari develops cognitive aspects through knowledge and self-awareness, while kalam insya’i shapes affective and behavioral dimensions through admonition, commands, and moral reflection, thereby fostering character building, social empathy, and individual responsibility.